Cooperation vs. Competition in Teams in the Business Environment - Snipes, Ellen Marie (My University, 2024)
Balancing cooperation and competition in the business environments is essential to fostering productive team dynamics and high performance. This research study examines how various factors including demographics (age, gender), employment status, personal styles, educational background field of study/industry, trust, monetary rewards, online environments, in-person environments, time working with an individual, and relationships relate with an individual’s inclination to either cooperate or compete in team environments. Many factors relate to understanding if an individual is cooperative or competitive but there also are mixed-motive situations (Levi, 2017). By analyzing data from a survey, classroom activity, interviews, and secondary research I concluded findings of cooperation vs. competition in business environments relating to students and business professionals.
Keywords: cooperation, competition, team dynamics